Hierarchical assembly of tryptophan zipper peptides into stress-relaxing bioactive hydrogels - Ashley K. Nguyen; Thomas G. Molley; Egi Kardia; Sylvia Ganda; Sudip Chakraborty; Sharon L. Wong; Juanfang Ruan; Bethany E. Yee; Jitendra Mata; Abhishek Vijayan; Naresh Kumar; Richard D. Tilley; et al. (Nature Communications, 2023)
Abstract Soft materials in nature are formed through reversible supramolecular assembly of biological polymers into dynamic hierarchical networks. Rational design has led to self-assembling peptides with structural similarities to natural materials. However, recreating the dynamic functional properties inherent to natural systems remains challenging. Here we report the discovery of a short peptide based on the tryptophan zipper (trpzip) motif, that shows multiscale hierarchical ordering that leads to emergent dynamic properties. Trpzip hydrogels are antimicrobial and self-healing, with tunable viscoelasticity and unique yield-stress properties that allow immediate harvest of embedded cells through a flick of the wrist. This characteristic makes Trpzip hydrogels amenable to syringe extrusion, which we demonstrate with examples of cell delivery and bioprinting. Trpzip hydrogels display innate bioactivity, allowing propagation of human intestinal organoids with apical-basal polarization. Considering these extensive attributes, we anticipate the Trpzip motif will prove a versatile building block for supramolecular assembly of soft materials for biotechnology and medicine.